TRANSIENT MODELING AND SIMULATION OF COMPACT PHOTOBIOREACTORS - Ribeiro, R. L. L.; Mariano, A. B.; Souza, J. A.; Vargas, J. V. C. (Revista de Engenharia Térmica, 2008)
In this paper, a mathematical model is developed to make possible the simulation of microalgae growth and its dependency on medium temperature and light intensity. The model is utilized to simulate a compact photobioreactor response in time with physicochemical parameters of the microalgae Phaeodactylum tricornutum. The model allows for the prediction of the transient and local evolution of the biomass concentration in the photobioreactor with low computational time. As a result, the model is expected to be a useful tool for simulation, design, and optimization of compact photobioreactors. Numerical solutions of the mathematical model are presented for the visualization of biomass concentration and total production. Several simulations were performed with temperatures ranging from 274 K to 300 K , and the maximum biomass production was achieved with an operating temperature of 294 K.